1999
DOI: 10.2114/jpa.18.101
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Physiological Responses and Type A Behavior Pattern.

Abstract: Abstract.The relationships between individual differences in psychophysiological responses and tendency of Type A behavior pattern (TABP) were investigated during mental arithmetic (MA) at a steady rhythm, challenging calculation (Uchida-Kraepelin serial addition test: UK test), music listening, and exposure to an 80 dB SPL of white noise. Each mental task was sustained for 5 minutes. Sixteen healthy Japanese adults, (10 males and 6 females) with an age from 18 to 36 years old volunteered for this study. The K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
(26 reference statements)
1
21
0
Order By: Relevance
“…Oishi et al 37 found that under stress conditions Type A behavior patterns determine short-term responses in physiological variables that are controlled by sympathetic nervous system, such as respiratory rate, skin resistance response, and heart rate variability. On the other hand, we have recently shown that in healthy adults cardiac autonomic task-induced reactivity and recovery are associated with carotid IMT.…”
Section: Discussionmentioning
confidence: 99%
“…Oishi et al 37 found that under stress conditions Type A behavior patterns determine short-term responses in physiological variables that are controlled by sympathetic nervous system, such as respiratory rate, skin resistance response, and heart rate variability. On the other hand, we have recently shown that in healthy adults cardiac autonomic task-induced reactivity and recovery are associated with carotid IMT.…”
Section: Discussionmentioning
confidence: 99%
“…Stressful thoughts may be associated with an increase in respiratory frequency (265), but personality type may be a contributing factor to respiratory responses to emotional stimulation as well (124,175). Performing mathematical calculations generally increases the respiratory, heart, and sympathetic activation rates (208). Imagining activities replicates many of the sympathetic and respiratory activities associated with the actual performance of the task (66).…”
Section: Cognitive and Emotional Activities That Interact With Breathingmentioning
confidence: 99%
“…Type A individuals display certain traits with the following special features: passionate and explosive in speech (loud voice and quick speech), hypervigilant and hyperactive, impatient and rushed for time, hard-driving and competitive, ambitious, hostile, and aggressive (Hugdahl, 1995;Lachar, 1993;Oishi et al, 1999;Palmero et al, 2001). On the other hand, Type B behavior pattern (Type B) indivisuals are those who exhibit a behavior pattern with a lower intensity/frequency of such traits/features.…”
Section: Introductionmentioning
confidence: 99%
“…According to studies dealing with Type A and Type B (Anderson and Lawler, 1995;Oishi et al, 1999;Ward et al, 1986;Williams et al, 1982), Type A indicates relatively enhanced sympathetic reactivity (i.e. increases in systolic blood pressure (SBP), heart rate (HR) and catecholamine secretion).…”
Section: Introductionmentioning
confidence: 99%